Christianity and Judaism under Islam in Medieval Iraq: Da’ûd al-Muqammas and Sa’d b. Mansûr Ibn Kammûna - Almbladh, Karin (Nordisk judaistik/Scandinavian Jewish Studies, 2008)
In the present paper two attitudes towards Christianity among Jews in Medieval Iraq are discussed, viz. Da’ûd al-Muqammas (second half of the 9th century) and Sa’d b. Mansûr Ibn Kammûna (second half of the 13th century). Da’ûd al-Muqammas was writing in a period when Christianity may have been an attractive alternative for intellectual Jews. His major work still available, ’Ishrûn Maqâla, "Twenty chapters", is an anti-Christian tract demonstrating the continuing validity of Judaism. Addressing a Gentile readership in his Tanqîh al-abhâth li’l-milal al-thalâth, "The examination of the inquiries into the three faiths", Sa’d b. Mansûr Ibn Kammûna upholds the validity of Judaism and Christianity against the claims of Islam in a period when Islam had been reduced to the same status as Judaism and Christianity in the early Mongol rule of Iraq.